Rancangan Database Jadwal Retensi Arsip dalam Penyusutan Arsip dengan Penggunaan Microsoft Access di Fakultas Ekonomi Universitas Negeri Padang - Iqbal, Harry; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
The purposes of this article are to describe about: the design of database records retention schedule in depreciation archives with the use of Microsoft Access at the Faculty of Economics, University of Padang. The method used in this paper is descriptive method. Data were collected through observation, interviews, and literature at the Faculty of Economics, University of Padang. Based on the discussion, it can be concluded that: (1) a general description of the archive in the depreciation schedule retenasi archives with the use of Microsoft Access at the Faculty of Economics, University of Padang as follows: Invitation Letter archive list, Snail Mail, Mail Important, SK. Rector, SK. Dean, Rector's Report, Report of the Dean, Employee Performance Report, Report of Activities, Academic Handbook, Handbook for Student Activities, Books Graduation, MOU (agreement / MoU), MOA (agreement), SK. Establishment of the Faculty, and SK. Establishment Program stored in the room administration; (2) the design process database retention schedule archives in depreciation archives with the use of Microsoft Access at the Faculty of Economics, University of Padang as follows: run Microsoft Access, create a table in Microsoft Access, queries, forms, reports and swithboard on Microsoft Access as the final display or The main menu database records retention schedule.Keyword: database, electronic archive.